Women in Attempt to Improve Economy of Coastal Communities (Case Study: Community Development Through Mentoring by the Mutiara Ru Group in Pegantungan Village) - Nurhidayati (Prospect: Jurnal Pemberdayaan Masyarakat, 2024)
Community development is a significant aspect of the Company's implementation of CSR programs. Community development programs carried out in Pegantungan Village studied in this journal are regarding the Empowerment of Coastal Women by assisting the Mutiara Ru SME (Small Medium Enterprise) group. The problem of unstable selling prices for marine products means that other productivity activities are needed to support the economic needs of village communities. The results of program activities carried out by PT PLN Nusantara Power – PLTU Suge Belitung show that through the programs, groups can be empowered, and women can fulfill the household economy.